Association of COPD candidate genes with CT emphysema and airway phenotypes in severe COPD - Kim, Woo Jin (2010)
The principal determining factors influencing the development of the airway disease and emphysema components of COPD have not been clearly defined. Genetic variability in COPD patients might influence the varying degrees of involvement of airway disease and emphysema. Therefore, we investigated genetic association of SNPs in COPD candidate genes for association with emphysema severity and airway wall thickness phenotypes. Polymorphisms in six candidate genes were analyzed in 379 subjects of the National Emphysema Treatment Trial (NETT) Genetics Ancillary Study with quantitative chest CT data. Genetic association with percent of lung below −950 hounsfield units (LAA950), airway wall thickness (WT), and derived square root wall area of 10 mm internal perimeter airways (SRWA) were investigated. Three SNPs in EPHX1, five SNPs in SERPINE2, and one SNP in GSTP1 were significantly associated with LAA950. Five SNPs in TGFB1, two SNPs in EPHX1, one SNP in SERPINE2, and two SNPs in ADRB2 were associated with airway wall phenotypes in NETT. In conclusion, several COPD candidate genes showed evidence for association with airway wall thickness and emphysema severity using CT in a severe COPD population. Further investigation will be required to replicate these genetic associations for emphysema and airway wall phenotypes.